REGISTER PEKERJA BANGUNAN DI DESA TEBANG KACANG KABUPATEN KUBU RAYA: KAJIAN SOSIOLINGUISTIK - Sari, Suci Permata; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
The discussion of this research includes the types of registers, register functions, and their implementation in Indonesia language learning at school. This research uses qualitative method. The data sources of this research are Javanes, Madurese, and Malay spoken by informants in Tebang Kacang Village, Kubu Raya Regency. The data collection techniques used are observation, free listening, recording, interview, and note taking. Based on the data that has been analyzed, There are 46 registers used by building workers, 20 closed register and 26 open registers. Instrumental registry functions 13 registers, regulatory functions 14 registers, representative functions 14 registers, interactive functions 20 registers, personal functions 10 registers, heuristic functions 5 registers, and no imaginary register function on building workers in the village of Tebang Kacang district of Kubu Raya. The implementation of the research is realized by making teaching modules for the Merdeka curriculum, especially the Indonesian language lessons for junior high school class VII odd semester.